Profil Permasalahan Umum Siswa Kelas XI dan Implikasinya dalam Program Bimbingan dan Konseling di SMA - Santoso Santoso; Yulius Mataputun; Densemina Yunita Wabdaron; Ahmad Sofyan (Cenderawasih Journal of Counseling and Education, 2022)
The present study aimed: 1) to describe the common problems of female students in grade XI, 2) to describe the common problems of male students in grade XI, 3) to describe the common problems of female and male students in grade XI. The research approach used by the researcher was descriptive type. This study identified common problems experienced by each grade XI student at SMA Negeri 2 Skanto, Keerom Jayapura Regency, Papua. The research sample was a saturated sample (all members of the population) totaling 135 students. Based on research findings on the common problems of female students, there were 55 people (92%) experiencing educational and teaching problems. In the common problem of male students, most or 25 people (58%) experienced personal problems. In the common problems of female and male students, most or 55 people (92%) experienced problems in education and teaching and 25 people (58%) experienced personal problems. It was concluded that a guidance and counseling program for female and male or grade XI Senior High School students is very highly required.